Neurogenesis potential of oligodendrocyte precursor cells from oligospheres and injured spinal cord - Zhao, Qing; Zhu, Yanjing; Ren, Yilong; Yin, Shuai; Yu, Liqun; Huang, Ruiqi; Song, Simin; Hu, Xiao; Zhu, Rongrong; Cheng, Liming; Xie, Ning (Frontiers in Cellular Neuroscience, 2022)
Severe traumatic spinal cord injury (SCI) leads to long-lasting oligodendrocyte death and extensive demyelination in the lesion area. Oligodendrocyte progenitor cells (OPCs) are the reservoir of new mature oligodendrocytes during damaged myelin regeneration, which also have latent potential for neurogenic regeneration and oligospheres formation. Whether oligospheres derived OPCs can differentiate into neurons and the neurogenesis potential of OPCs after SCI remains unclear. In this study, primary OPCs cultures were used to generate oligospheres and detect the differentiation and neurogenesis potential of oligospheres. In vivo, SCI models of juvenile and adult mice were constructed. Combining the single-cell RNA sequencing (scRNA-seq), bulk RNA sequencing (RNA-seq), bioinformatics analysis, immunofluorescence staining and molecular experiment, we investigated the neurogenesis potential and mechanisms of OPCs in vitro and vivo. We found that OPCs differentiation and oligodendrocyte morphology were significantly different between brain and spinal cord. Intriguingly, we identify a previously undescribed findings that OPCs were involved in oligospheres formation which could further differentiate into neuron-like cells. We also firstly detected the intermediate states of oligodendrocytes and neurons during oligospheres differentiation. Furthermore, we found that OPCs were significantly activated after SCI. Combining scRNA-seq and bulk RNA-seq data from injured spinal cord, we confirmed the neurogenesis potential of OPCs and the activation of endoplasmic reticulum stress after SCI. Inhibition of endoplasmic reticulum stress could effectively attenuate OPCs death. Additionally, we also found that endoplasmic reticulum may regulate the stemness and differentiation of oligospheres. These findings revealed the neurogenesis potential of OPCs from oligospheres and injured spinal cord, which may provide a new source and a potential target for spinal cord repair.